UPAYA PENCEGAHAN DAN PENGENDALIAN COVID-19 STIKES KARSA HUSADA GARUT - Perceka, Andhika Lungguh; engkus kusnadi; Hasbi Taobah Ramdani; Dede Suharta; Desy Syswianti; N. Ai Erlinawati; Wahyudin (Jurnal Pengabdian Masyarakat DEDIKASI, 2020)
Corona virus Disease 2019 (COVID-19) is a new type of disease that has never been previously identified in humans. The virus that causes COVID-19 is called Sars-CoV-2. Corona viruses are zoonotic (transmitted between animals and humans). The community service program The Covid 19 Prevention and Control Program aims to increase the knowledge and ability of the community in dealing with the Covid 19 pandemic that has spread in society and to know the level of community compliance with 3M (using masks, maintaining distance and washing hands). The target of this service activity is the people who work in the market, the terminal in Garut as many as 300 respondents. The method of this activity was a one-by-one or interpersonal counseling approach. The team made teaching aids in the form of pamphlets, brochures, hand sanitizers themselves in the D3 Pharmacy Study Program laboratory to be distributed to the public. Each team that provided masks and handsanitizers, gave direct instructions on how to use them. This was done because it could not be done in a crowd as a social distancing effort in the interest of preventing the spread of Covid-19 in society. Based on the results of counseling on prevention and control of covid 19, the results in the Ciawitali market that the percentage of community compliance for 3M before 20% counseling increased to 60% of 100 respondents, in the Wanaraja market the percentage of community compliance for 3M before 30% counseling increased to 50% of 100 respondents, At the Ciawitali Terminal, the percentage of community compliance for 3M before counseling was 30% increased to 74% of 50 respondents, in Tarogong Square the percentage of community compliance for 3M before extension 50% increased to 84% of 50 respondents. Thus, this mentoring activity can be said to be successful because it is able to increase the knowledge and abilities of participants in participating in community service activities.